Application of a heterogeneous adsorbent (HA) for the removal of hexavalent chromium from aqueous solutions: Kinetic and equilibrium modeling - Srivastava V.; Shekhar M.; Gusain D.; Gode F.; Sharma Y.C. (My University, 2025)
In the present study, a heterogeneous adsorbent material (HA) was used as an adsorbent for the removal of Cr(VI) from aqueous solutions at laboratory scale. Cr(VI) containing water was treated with heterogeneous adsorbent(HA).Chromium solutions of various initial concentrations were treated with adsorbent in batch mode experiments to investigate the adsorption characteristics of heterogeneous adsorbent (HA). Kinetics of adsorption of Cr(VI) ions on adsorbent was investigated by using pseudo first order and second order kinetic models. Removal processes were found to be governed by pseudo second order model. Intraparticle diffusion model was also analyzed for this system. Removal was found to be increased by increasing the temperature from 298 to 318 K which indicates the endothermic nature of the process. Various two parameter isotherm models viz. Langmuir, Freundlich, Elovich, Tempkin, Dubnin–Raduskevich (D–R), Harkin–Jura and BET isotherm were applied on resultant data for equilibrium modeling. It was observed that heterogeneous adsorbent (HA) particles were highly efficient for the removal of Cr(VI). © 2013